2013
DOI: 10.2147/rrn.s43272
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomic impact of use of the probiotic Lactobacillus reuteri DSM 17938 for prevention of necrotizing enterocolitis in extremely low-birth-weight infants

Abstract: Background:A recent study showed that use of Lactobacillus reuteri as probiotic prophylaxis decreased the necrotizing enterocolitis (NEC) rate from 15.1% to 2.5% in neonates with birth weight below 1000 g. Given the controversies surrounding use of probiotics in neonatal intensive care units, we address one additional aspect of routine implementation of probiotics for NEC prophylaxis -the pharmacoeconomic impact. Methods: Using data from our initial published experience, and continuing data collection after in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…The Prophylactic Probiotics to Extremely Low Birth Weight Prematures (PROPEL) RCT was reported as two separate manuscripts. 45,46 The non-RCTs by Gal et al, 47 Dimaguila et al, 48 and Hunter et al 49 were three separate publications focusing on different outcomes from the same study (Table 2). Coleta et al 50 reported shorter TFF and improved gastrointestinal tolerance after LR supplementation.…”
Section: Selection Characteristics and Quality Of Studiesmentioning
confidence: 99%
“…The Prophylactic Probiotics to Extremely Low Birth Weight Prematures (PROPEL) RCT was reported as two separate manuscripts. 45,46 The non-RCTs by Gal et al, 47 Dimaguila et al, 48 and Hunter et al 49 were three separate publications focusing on different outcomes from the same study (Table 2). Coleta et al 50 reported shorter TFF and improved gastrointestinal tolerance after LR supplementation.…”
Section: Selection Characteristics and Quality Of Studiesmentioning
confidence: 99%